TLR-Mediated B Cell Defects and IFN-α in Common Variable Immunodeficiency - Yu, Joyce E.; Zhang, Li; Radigan, Lin; Sanchez-Ramon, Silvia; Cunningham-Rundles, Charlotte (Journal of clinical immunology, 2012)
Common variable immune deficiency (CVID) B cells have impaired responses to TLR7 and TLR9 agonists including poor cell proliferation, loss of cytokine production, and failure to produce IgG or IgA. We show that TLR7- or 9-activated B cells from CVID subjects with >0.5% peripheral isotype-switched CD27 + B cells (group 2) have increased mature Cγ1 and Cγ2 heavy-chain mRNA transcripts compared to subjects who have <0.5% isotype-switched cells (group 1). While TLR-stimulated CVID plasmacytoid dendritic cells for all subjects had impaired IFN-α production, TLR7 or TLR9 stimulation in the presence IFN-α normalized isotype-switched CD27 + B cells, enhanced activation-induced cytidine deaminase mRNA, and significantly improved IgG production only for group 2 subjects. IFN-α also upregulated TLR7 and TLR9 mRNA expression comparable to normal levels in B cells of group 2 subjects, indicating that the loss of IFN-α could be a significant component of the B-cell defect for these subjects.